178Depression but not physical activity mediates the fatigue-mental quality of life relationship in multiple sclerosis. (2nd September 2021) - Fidao, Alexander; De Livera, Alysha; Weiland, Tracey; Jelinek, George; Neate, Sandra; Nag, Nupur; Simpson-Yap, Steve
Abstract: Background: Fatigue is among the most prevalent symptoms of multiple sclerosis (MS), and significantly detrimental to mental quality of life. We examined the role of depression and physical activity as mediators in the fatigue-QoL relationship in MS. Methods: Using an international study cohort measuring a wide range of lifestyle and clinical factors, determinants of fatigue (Fatigue Severity Scale) and mental quality of life (MSQoL-54; QoL) were assessed in 2, 104 participants using log-binomial and linear regression, respectively. Structural equation modelling (SEM) was used to assess the mediating role of depression and physical activity between fatigue and mental QoL. Results: The median mental QoL score in the sample was 73.8/100. The mean fatigue score was 40.5/63, with 65.6% having clinically significant fatigue. In SEM analyses evaluating depression as a mediator of the fatigue-QoL relationship, mental QoL was 14.17-points lower in those with clinically significant fatigue, of which the indirect effect via depression accounted for over 30.8% (p < 0.001). This mediation effect was most pronounced for the Role Limitations from Emotional Issues (44.9%, p < 0.001) and Emotional Wellbeing (41.6%, p < 0.001) subdomains. Evaluating physical activity as a mediator of the fatigue-QoL relationship, mental QoL was 11.03-points lower in those with clinically significant fatigue, of which the indirect effect via physical activity accounted for only 1.0% (p = 0.001). Conclusions: This study provides evidence that depression accounts for a majority of the fatigue-mental QoL relationship, while physical activity only plays a small role. While replication and longitudinal studies are required for validation, our findings may inform the development of treatments for reducing the impacts of fatigue and improving QoL in people with MS. Key messages: Fatigue's negative impact on emotional quality of life in multiple sclerosis is not a function of reduced ambulation but instead its impact on depression. Reducing depression may thus markedly improve quality of life in this population.